Promoter hypermethylation promotes the binding of transcription factor NFATc1, triggering oncogenic gene activation in pancreatic cancer - Wu, Yenan; Kröller, Lea; Miao, Beiping; Boekhoff, Henning; Bauer, Andrea; Büchler, Markus W.; Hackert, Thilo; Giese, Nathalia; Taipale, Jussi; Hoheisel, Jörg D. (Cancers, 2021)
Studies have indicated that some genes involved in carcinogenesis are highly methylated in their promoter regions but nevertheless strongly transcribed. It has been proposed that transcription factors could bind specifically to methylated promoters and trigger transcription. We looked at this rather comprehensively for pancreatic ductal adenocarcinoma (PDAC) and studied some cases in more detail. Some 2% of regulated genes in PDAC exhibited higher transcription coupled to promoter hypermethylation in comparison to healthy tissue. Screening 661 transcription factors, several were found to bind specifically to methylated promoters, in particular molecules of the NFAT family. One of them—NFATc1—was substantially more strongly expressed in PDAC than control tissue and exhibited a strong oncogenic role. Functional studies combined with computational analyses allowed determining affected genes. A prominent one was gene ALDH1A3, which accelerates PDAC metastasis and correlates with a bad prognosis. Further studies confirmed the direct up-regulation of ALDH1A3 transcription by NFATc1 promoter binding in a methylation-dependent process, providing insights into the oncogenic role of transcription activation in PDAC that is promoted by DNA methylation.
Gesehen am 18.11.2021
This article belongs to the special issue "Unraveling an aggressive cancer: the role of epigenetics in pancreas cancer"